Polish Language Maintenance and Transmission in Finnish Diaspora: A Study of Family Dynamics and Cultural Influences - Izabela Jakubek-Głąb (Languages)
The Polish diaspora is represented worldwide. Yet, little is known about Polish language and culture maintenance in Finland. However, the language practices of Polish families living there are worth being investigated, particularly in relation to language maintenance and transmission. This research aims to explore how families engage with the Polish language and what factors contribute to its preservation. The study focuses on the role of family dynamics, including interactions, communication patterns, and language choices within the family unit. The research is built on a survey of representatives of the Polish diaspora in Finland and a qualitative case study of a Polish family living in Finland. It uses content and descriptive analyses. The results identify effective strategies and interventions that can enhance the long-term vitality of the Polish language in diaspora communities. Cultural influences, such as traditions, values, and identities, are considered in relation to the sustainability of language development.